Mitochondrial phylogenomics reveals deep relationships of scarab beetles (Coleoptera, Scarabaeidae) - Guo, Shibao; Lin, Xingyu; Song, Nan (PloS one, 2022)
In this study, we newly sequenced the complete mitochondrial genomes (mitogenomes) of two phytophagous scarab beetles, and investigated the deep level relationships within Scarabaeidae combined with other published beetle mitogenome sequences. The complete mitogenomes of Dicronocephalus adamsi Pascoe (Cetoniinae) and Amphimallon sp. (Melolonthinae) are 15,563 bp and 17,433 bp in size, respectively. Both mitogenomes have the typical set of 37 genes (13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes) and an A+T-rich region, with the same gene arrangement found in the majority of beetles. The secondary structures for ribosomal RNA genes ( rrnL and rrnS ) were inferred by comparative analysis method. Results from phylogenetic analyses provide support for major lineages and current classification of Scarabaeidae. Amino acid data recovered Scarabaeidae as monophyletic. The Scarabaeidae was split into two clades. One clade contained the subfamilies Scarabaeinae and Aphodiinae. The other major clade contained the subfamilies Dynastinae, Rutelinae, Cetoniinae, Melolonthinae and Sericini. The monophyly of Scarabaeinae, Aphodiinae, Dynastinae, Cetoniinae and Sericini were strongly supported. The Scarabaeinae was the sister group of Aphodiinae. The Cetoniinae was sister to the Dynastinae + Rutelinae clade. The Melolonthinae was a non-monophyletic group. The removal of fast-evolving sites from nucleotide dataset using a pattern sorting method (OV-sorting) supported the family Scarabaeidae as a monophyletic group. At the tribe level, the Onthophagini was non-monophyletic with respect to Oniticellini. Ateuchini was sister to a large clade comprising the tribes Onthophagini, Oniticellini and Onitini. Eurysternini was a sister group of the Phanaeini + Ateuchini clade.